Effect of humour therapy on psychotropic medication use in nursing homes. (17th March 2016) - Leow, Jerome BY; Pont, Lisa; Low, Lee‐Fay
Abstract : Aim: The aim of this study was to assess the effect of Play Up humour therapy on antipsychotic, benzodiazepine and antidepressant use in Australian nursing homes. Methods: Play Up is a humour therapy program that has been implemented in Australian nursing homes. This study was an uncontrolled retrospective review of psychotropic medication charts of 406 residents in thirty‐three nursing homes before and after 12 weeks of participation in Play Up. Prevalence and mean daily equivalent doses of psychotropic medication use were analysed. Results: There were significant reductions from before to after the Play Up program in the prevalence of any psychotropic medication use, antipsychotic use and benzodiazepine use ( P = 0.001, 0.02, 0.007, respectively). Mean daily dose equivalents of pro re nata (PRN) antipsychotics and PRN benzodiazepines significantly reduced over time ( P = 0.007; P = 0.001). Conclusions: Play Up was associated with an overall decline in the use of psychotropic medications. Further trials are required to confirm and better define this association.